Intra-articular injection of platelet-rich plasma for knee osteoarthritis: scientific technical opinion on the use (Research, Society and Development, 2021)
There are several publications on this topic available in the scientific community, with the vast majority advocating the use of Plasma Rich in Platelets for the treatment of knee osteoarthritis, but there is no consensus among the authors on the characteristics of use and manipulation, such as how to prepare the substance and how often to administer it, so there are several favorable reports, but each with a different clinical approach. Objective: perform a literature review on osteoarthritis and analyze the scientific evidence currently available on the efficacy and safety of intra-articular injection of platelet-rich plasma for knee osteoarthritis. Method: literature review, based on systematic reviews published in the Medical Literature Analysis and Retrieval System Online. Results: The technique in question has shown itself to be promising in the treatment, a reason that was not contraindicated for use in the clinical environment, but aiming at incorporation in any medical service, it will be necessary to define the usage pattern, as well as clinical tests. Conclusion: In this way, the present opinion is not favorable to the recommendation of use in the state of the art existing at the time, recommending the creation of protocols and new studies for a possible incorporation later.